The Removal of Phenol and Its Derivatives from Aqueous Solutions by Adsorption on Petroleum Asphaltene - Omer El-Amin Ahmed Adam; Ammar Hani Al-Dujaili (Journal of Chemistry)
This research describes the adsorption of phenol and o-substituted phenols and xylenol isomers on petroleum asphaltenes from aqueous solution. The results revealed that the adsorption equilibrium data were best fitted with the generalized and Freundlich isotherms. For o-substituted phenols, it was found that electron-withdrawing groups increase the adsorption capacity. The uptake of these phenols decreases in the order: o-nitrophenol > o-chlorophenol > o-aminophenol > o-cresol > phenol, while the adsorption of xylenol isomers decreases in the order: 2,6-xylenol > 2,5-xylenol > 3,5-xylenol > 3,4-xylenol. Batch equilibrium results at different temperatures suggest that the adsorption of 2,6-xylenol and 3,5-xylenol onto asphaltene is an endothermic process, values obtained were positive indicating a nonspontaneous process with increasing randomness at the solid-solution interface. The influence of solution pH on the adsorption of 3,5-xylenol on asphaltenes was also investigated. The adsorption process was found to be independent on the solution pH. The adsorption capacity of 3,5-xylenol was found to increase with the decrease in particle size of the adsorbent.